Log(4x-5)=Log(2x+7)

Simple and best practice solution for Log(4x-5)=Log(2x+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Log(4x-5)=Log(2x+7) equation:


Simplifying
Log(4x + -5) = Log(2x + 7)

Reorder the terms:
goL(-5 + 4x) = Log(2x + 7)
(-5 * goL + 4x * goL) = Log(2x + 7)
(-5goL + 4goxL) = Log(2x + 7)

Reorder the terms:
-5goL + 4goxL = goL(7 + 2x)
-5goL + 4goxL = (7 * goL + 2x * goL)
-5goL + 4goxL = (7goL + 2goxL)

Solving
-5goL + 4goxL = 7goL + 2goxL

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '-7goL' to each side of the equation.
-5goL + -7goL + 4goxL = 7goL + -7goL + 2goxL

Combine like terms: -5goL + -7goL = -12goL
-12goL + 4goxL = 7goL + -7goL + 2goxL

Combine like terms: 7goL + -7goL = 0
-12goL + 4goxL = 0 + 2goxL
-12goL + 4goxL = 2goxL

Add '-2goxL' to each side of the equation.
-12goL + 4goxL + -2goxL = 2goxL + -2goxL

Combine like terms: 4goxL + -2goxL = 2goxL
-12goL + 2goxL = 2goxL + -2goxL

Combine like terms: 2goxL + -2goxL = 0
-12goL + 2goxL = 0

Factor out the Greatest Common Factor (GCF), '2goL'.
2goL(-6 + x) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'goL' equal to zero and attempt to solve: Simplifying goL = 0 Solving goL = 0 Move all terms containing g to the left, all other terms to the right. Simplifying goL = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(-6 + x)' equal to zero and attempt to solve: Simplifying -6 + x = 0 Solving -6 + x = 0 Move all terms containing g to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = 0 + 6 Combine like terms: -6 + 6 = 0 0 + x = 0 + 6 x = 0 + 6 Combine like terms: 0 + 6 = 6 x = 6 Add '-1x' to each side of the equation. x + -1x = 6 + -1x Combine like terms: x + -1x = 0 0 = 6 + -1x Simplifying 0 = 6 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 35/30=N/6 | | -x+3(7)=23 | | 4a+2b+4c=40 | | 4(x+5)+(x-3)=5-x | | 10+32=216-2a | | Log(5x+13)=1 | | 6a+8b=40 | | 6a+8b-40=0 | | 10/5a=2 | | 2x-100=135-3x | | F(x)=x^4+2x^3+x^2-4 | | 2(w-9)=9w-32 | | 90/125 | | 4/x-8=-2 | | 4x/4-2=-2 | | 7x-1/4-1/7(2x-1-x/2)=4 | | 25d^2-4=0 | | (3x)+(5x-12)+(5x+18)=180 | | 25d^2=0 | | 20x^3-40x^2+80x=0 | | 8x-15=4x-11 | | b^2+8b=-12 | | x+(2x+15)+(4x-10)=180 | | 25a=10x^2 | | 18n^2+60n+42=0 | | 38=w/2 | | 4S-s= | | 2sinx-5cosx=-1 | | x+0.145x=128034 | | ax+ay=12 | | 10x-100=3x-9 | | log[4]7x+2=5 |

Equations solver categories